2013
DOI: 10.1177/1028315312474315
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking International Migration of Human Capital and Brain Circulation

Abstract: This article examines the dynamics of brain circulation through a historical review of the debates over international migration of human capital and a case study on Chinese-Canadian academics. Interviews with 22 Chinese-Canadian professors who originally came from China provide rich data regarding the possibilities and problems of the contemporary global mobility. The findings indicate that brain circulation is possible in the case of Chinese-Canadian academics but that certain conditions and factors, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…Perhaps China, with GDP growth in 2011 at 9.5 percent, is a classic example of brain circulation, and one the most studied as a result of it. Blachford and Zhang () uncovered that an estimated 700,200 individuals left China to study overseas between 1978 and 2003 while only 172,800 returned during that same time (Ministry of Education, the People's Republic of China ). Now, with a faster growing economy and greater opportunities, the trend has reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps China, with GDP growth in 2011 at 9.5 percent, is a classic example of brain circulation, and one the most studied as a result of it. Blachford and Zhang () uncovered that an estimated 700,200 individuals left China to study overseas between 1978 and 2003 while only 172,800 returned during that same time (Ministry of Education, the People's Republic of China ). Now, with a faster growing economy and greater opportunities, the trend has reversed.…”
Section: Discussionmentioning
confidence: 99%
“…This fact not only determines the choice of destination, but can also trigger the entire migration process [Jons, 2009]. As an alternative to physical movement, there are various formats of scientific networking, when scientific migrants stay interested in their home countries' knowledge production and maintain the communication with former colleagues [Ciumasu, 2010;Blachford, Zhang, 2014].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Early definitions of brain circulation refuted the notion that highly skilled workers would remain overseas permanently, arguing that such migrants would eventually circulate back to their home communities (Gaillard and Gaillard, ). Yet recent studies have shown that in reality, most highly educated professionals never return “home,” choosing instead to settle outside their countries of origin (Blachford and Zhang, ). As a result, researchers have sought to understand whether highly skilled migrants can contribute to their home communities from a distance, moving beyond the assumption that such “brains” are lost when they leave national territories (Fahey and Kenway, ; Mahroum, Eldridge, and Daar, ; Meyer, ; Saxenian, ).…”
Section: Brain Circulation and Developmentmentioning
confidence: 99%
“…In the case of migrant academics, governments have launched a wide range of programmes, providing research funding, institutional support, and opportunities for short-term visits (Blachford and Zhang, 2014;Xiang, 2011). Researchers argue that migrant academics often express a desire to help improve teaching and research in universities within their home countries, and suggested that well-planned programmes should provide them with the opportunity to do so effectively (Cohen, Duberley and Ravishankar, 2015).…”
Section: Brain Circulation and Developmentmentioning
confidence: 99%